Conformational Study of an Artificial Metal‐Dependent Regulation Site for Use in Designer Proteins1. Issue 8 (21st May 2013) - Oheix, Emmanuel; Spencer, Neil; Gethings, Lee A.; Peacock, Anna F. A.
Abstract This report describes the dimerisation of glutathione, and by extension, other cysteine‐containing peptides or protein fragments, with a 5, 5'‐disubstituted‐2, 2'‐bipyridine or 6, 6''‐disubstituted‐2, 2':6', 2''‐terpyridine unit. The resulting bipy‐GS2 and terpy‐GS2 were investigated as potential metal ion dependent switches in aqueous solution, and were found to predominantly adopt the transoïd conformation at physiological pH. Metal complexation with CuII and ZnII at this pH has been studied by UV/Vis, CD, NMR and ion‐mobility mass spectrometry. ZnII titrations are consistent with the formation of a 1:1 ZnII:terpy‐GS2 complex at pH 7.4, but bipy‐GS2was shown to form both 1:1 and 1:2 complexes with the former being predominant under dilute micromolar conditions. Formation constants for the resulting 1:1 complexes were determined to be log KM 6.86 (bipy‐GS2) and 6.22 (terpy‐GS2), consistent with a higher affinity for the unconstrained bipyridine, compared to the strained terpyridine. CuII coordination involves the initial formation of 1:1 complexes, followed by 1.5Cu:1bipy‐GS2 and 2Cu:1terpy‐GS2 complexes at micromolar concentrations. Binding constants for formation of the 1:1 complexes (log KM 12.5 (bipy‐GS2); 8.04 and 7.14 (terpy‐GS2)) indicate a higher affinity for CuII than ZnII. Finally, ion‐mobility MS studies detected the free ligands in their protonated form, and were consistent with the formation of two different Cu adducts with different conformations in the gas‐phase. We illustrate that the bipyridine and terpyridine dimerisation units can behave like conformational switches in response to Cu/Zn complexation, and propose that in future these can be employed in synthetic biology with larger peptide or protein fragments, to control large scale folding and related biological function.